The effect of Ramadan fasting on plaque count of Streptococcus Mutans in patients wearing fixed orthodontic appliance. A clinical study (Mustansiria Dental Journal, 2019)
Aim: This clinical study is to investigate the effect of fasting (Sawm) Ramadan on thecount of streptococcus mutans in plaque surrounding fixed orthodontic appliances.Materials and Methods: Fifteen patients with orthodontic appliances wereparticipated in this study. Plaque specimens were collected from those patients attwo occasions, during Rmadan fasting (Sawm) and after they break there fastingafter Ramadan. The plaque Streptococcus mutans number of colony-formingunits (CFU) was analyzed by using Dentocult SM Strip mutans test.Results: This study demonstrated highly significant difference in Streptococcusmutans (CFU) counts in plaque between the values obtained from fasting patientsduring Ramadan and when they are breaking the fast after Ramadan.Conclusions: during Ramadan fasting, persons change timing and types of their foodand beverages consuming as well as teeth cleaning habits. Therefore orthodontistshould be aware of their patients’ oral hygiene during Ramadan by promoting andmaintaining satisfactory teeth cleaning during fasting (Sawm) and Iftar hours.